2006
DOI: 10.1002/ijc.22062
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of EMMPRIN expression in human tumors

Abstract: Extracellular matrix metalloproteinase inducer expressed by tumor cells stimulates peritumoral fibroblasts to produce matrix metalloproteinases, thus contributing to tumor invasion and metastasis. To assess its suitability as potential therapeutic target, the overall incidence of EMMPRIN expression in normal and neoplastic tissues was analyzed. EMMPRIN expression was detected immunohistochemically using monoclonal antibodies MEM-M6/1 and HIM6 and tissue microarrays with 2,348 and 608 tissue samples from 129 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
174
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(192 citation statements)
references
References 51 publications
15
174
1
2
Order By: Relevance
“…It is believed to have a significant role in the development, differentiation and remodeling of many normal tissues including the lung, thymus, retina, skin, cornea and nervous system (Renno et al, 2002;Betsuyaku et al, 2003;Gabison et al, 2005;Nabeshima et al, 2006). However, it is in the field of cancer that EMMPRIN has garnered most interest because of its consistently high levels of expression on the surface of various tumors, including lung tumors, and because of its correlation with poor prognosis (Caudroy et al, 1999;Davidson et al, 2003;Yan et al, 2005;Riethdorf et al, 2006;Als et al, 2007;Sienel et al, 2008). EMMPRIN expression has also been linked to tumor metastasis as it is one of the most constantly upregulated mRNAs in bone marrow metastatic cells in lung, prostate and breast cancer (Klein et al, 2002;Reimers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is believed to have a significant role in the development, differentiation and remodeling of many normal tissues including the lung, thymus, retina, skin, cornea and nervous system (Renno et al, 2002;Betsuyaku et al, 2003;Gabison et al, 2005;Nabeshima et al, 2006). However, it is in the field of cancer that EMMPRIN has garnered most interest because of its consistently high levels of expression on the surface of various tumors, including lung tumors, and because of its correlation with poor prognosis (Caudroy et al, 1999;Davidson et al, 2003;Yan et al, 2005;Riethdorf et al, 2006;Als et al, 2007;Sienel et al, 2008). EMMPRIN expression has also been linked to tumor metastasis as it is one of the most constantly upregulated mRNAs in bone marrow metastatic cells in lung, prostate and breast cancer (Klein et al, 2002;Reimers et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…14 It is highly up-regulated in many malignant cancer cells and is thought to contribute to cell survival, invasion, metastasis, and multidrug resistance. 15 Studies targeting Bsg to prevent tumor growth using RNAi techniques have achieved successful outcomes. 16 -19 Along with MMPs, Bsg is also involved in the production of vascular endothelial growth factor and hyaluronan.…”
mentioning
confidence: 99%
“…Various physiological processes might be influenced by anti-EMMPRIN therapy (12), such as proliferation and differentiation of epithelial cells (20)(21)(22), fertilization (23), differentiation and activation of immune cells (24)(25)(26), integrinmediated adhesion of myocytes of the left heart ventricle to basement membrane components (27), selective transport processes in endothelial cells to maintain the blood-brainbarrier function (28), erythrocyte maturation (29) or wound healing (30). Accordingly, the side effects of target therapy using CD147 conjugates should be evaluated carefully.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of tumor-derived EMMPRIN in tumor angiogenesis through stimulation of MMPs and VEGF production was demonstrated by Tang et al (11), suggesting that CD147 could represent a key molecule in tumor cell invasion and metastasis. To assess its putative role as a target for anticancer therapies, Riethdorf et al (12), analyzed the overall incidence of CD147 expression in a wide spectrum of normal and tumor tissues. They showed that CD147 expression was detected frequently in the vast majority of human malignancies and also in a subset of benign tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation